Decolonizing bodies and emotions: a dispute with the expropriatory reason - Rebeca Beatriz Cena (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
The current issue of the Latin American Journal of Studies on Bodies, Emotions and Society (RELACES) entitled “Decolonizing bodies and emotions: a dispute with the expropriatory reason” gathers a series of articles framed within those problematizations which, from different approaches (the ways of feeling beauty and body aesthetics; the pain of “victims” of human rights; the different ways to conceive health and “the medicinal”; the conceptions of precarity; the shapes adopted by individual and social fear, and breaks as ways of regulating emotions in present capitalism), analyze the assumptions of the western reason as the reason par excellence.